Penerapan Metode Simple Additive Weighting dalam Menentukan Perguruan Tinggi Negeri - Muhammad Dedi Irawan; Yustria Handika Siregar; Sity Tree Adinda Tambunan; Muhammad Artha Ardika (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
World University Ranking is a system tool that functions to measure and assess all the best universities around the world (World Class University) which aims to advance all Universities through websites owned by each University. There are several problems in choosing a college. The selection of campuses or State Universities (PTN) is still often a problem or obstacle for every prospective student and parent to choose further education for the future of their children, especially as we often know that there are many universities in Indonesia. Indonesia ranges from state universities to private universities. One of the efforts in the selection recommendations made to facilitate this is to conduct an assessment of the best PTN. In this study, the Simple AdditiveWeighting (SAW) method was applied to the best college recommendation system. The criteria used are Tuition Fees, Academic Reputation, Employer Reputation, Teaching, Research, and Citation. After the criteria are determined, the next process is theranking process of the existing alternatives. The results of each method can provide recommendations for students or parents in choosing a college.